Impact of liquidity creation on the stability and profitability of banks: A case study of Vietnam - Phan, Thu Hien (Journal of Finance - Marketing Research, 2025)
Liquidity creation is a core and essential function of banks that affects their profitability and stability. This study measures the liquidity creation of Vietnamese banks during the period 2014–2023 using the comprehensive measurement approach developed by Berger and Bouwman (2009). Furthermore, the results indicate that banks that create more liquidity tend to be less stable and less profitable. The study also finds that changes in bank capital play a moderating role, weakening the impact of liquidity creation on bank stability. Based on the findings, the study emphasizes the importance of aligning bank liquidity creation with regulatory standards to enhance financial stability. In particular, banks should comply with the Basel III framework, especially the Liquidity Coverage Ratio (LCR) and Net Stable Funding Ratio (NSFR), which are designed to limit excessive liquidity creation and reduce systemic risk. These standards require banks to maintain a sustainable structure of assets and liabilities and hold sufficient high-quality liquid assets. Given that Basel III regulations are more comprehensive and complex than previous frameworks, the successful implementation in Vietnam will require not only the commitment and capacity of individual banks, but also clear and specific guidance from the State Bank of Vietnam to ensure consistency and effectiveness in practice.